Comparison of the ductal carcinoma in situ between White Americans and Chinese Americans. Issue 3 (22nd January 2021) - Kuang, Xin-Wen; Sun, Zhi-Hong; Song, Jun-Long; Zhu, Zhanyong; Chen, Chuang
Abstract : Abstract: Currently, the wide-spread use of screening mammography has led to dramatic increases in ductal carcinoma in situ (DCIS). However, DCIS of Chinese Americans, the largest Asian subgroup in American, has rarely been comprehensively studied over the past decade. This work compared the DCIS characteristics and prognosis of Chinese American patients with White Americans in the USA to determine the characteristics and prognosis of DCIS patients of Chinese Americans. The data were obtained using the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) data. The diagnosis and treatment variables between the two groups were compared by means of Chi-square tests. Survival was determined with the use of the Kaplan–Meier method and the multivariable Cox proportional hazard regression model. From 1975 to 2016, 81, 745 White Americans and 2069 Chinese Americans were diagnosed with ductal carcinoma in situ. Compared with the white patients, the Chinese Americans were younger ( P  < .001) with smaller tumors ( P  < .001) and higher family income ( P  < .001). DCIS patients of Chinese American group accounted for a higher percentage of all breast cancers than the whites ( P  < .001). In the multivariable Cox proportional hazard regression analysis, Chinese American was an independent favorable prognostic factor in terms of overall survival (OS) (HR, 0.684; 95% CI, 0.593–0.789; P  < .001) compared with the white group. In conclusion, DCIS characteristics of the Chinese group, which exhibited a higher proportion of younger age, a higher DCIS ratio, and a better prognosis, were distinct from those of the White Americans.